PENGGUNAAN MEDIA KARTU DOMINO HIDROKARBON UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR SISWA DI KELAS X.10 SMA NEGERI 5 PEKANBARU - Yessy Asnovida Amri; Asmadi M.Noer; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research problem that the writer found is that chemistry learning at class X.10 of SMAN 5 Pekanbaru is not condusive yet. In learning process, students are only as listeners and write notes if teacher write something on board. During learning process, students seldom ask a question. This research is aimed to know the improvement of students learning activity and mastery learning by using Hydrocarbon domino card at X.10 class of SMAN 5 Pekanbaru in academic year 2015/2016. This research is a class action research with two cycles in research design. The sample of this research was X.10 class which was given an action for improvement in learning process by using Hydrocarbon domino card media. The data collection was conducted by observing and giving tests. The data analysis technique was conducted descriptively by using percentage technique. Based on the result of the data analysis, it can be concluded that the use of Hydrocarbon domino card media can improve students learning activity and completeness at X.10 class of SMAN 5 Pekanbaru. It can be seen by the improvement of students learning activity from 69,72% at the first cycle to 85,97% at the second cycle and students learning completeness from 87,50% at the first cyle to 100% at the second cycle.Key Words : Hydrocarbon Domino Card Media, Learning Completeness, Hydrocarbons